Stability Analysis of Uncertainty Linear Systems Described by Fuzzy Characteristic Equations. Issue 1 (8th February 2012) - Hallaji, Majid; Zare, Assef; Kamyad, Ali Vahidian
Abstract This paper uses Kharitonov's theorem to present a new idea for assessment of the stability of linear systems that are described by fuzzy differential equations, while system uncertainty is expressed as fuzzy convex sets for coefficients of the characteristic equation. The paper then deals with determination of stability margins and the design of classical robust controllers of fuzzy type for those systems. In each part, illustrative examples and simulation results are provided.